2003
DOI: 10.1007/s11738-003-0011-6
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of [3-3H]oleanolic acid in Calendula officinalis L. roots

Abstract: The radioactive precursor, [3-3H]oleanolic acid was administrated to excised roots from four weeks old Calendula offi'cinalis L. plants. Transformations of this compound into two series of its glycosides, i.e. glucosides and glucuronides were investigated. For the first time it has been shown that both series of oleanolic acid glycosides are synthesized in roots of young marigold plants. The pathway of their biosynthesis seems to be similar, although not identical, to the pathway occurring in green organs of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Our latest results have shown that both series of glycosides are synthesized in roots of young marigold plants (Ruszkowski et al, 2003). The pathway of their biosynthesis is similar, although not identical, to the pathway occurring in green organs (Figure 2).…”
Section: Biosynthesis and Metabolism Of Oleanolic Acid Glycosidesmentioning
confidence: 70%
See 1 more Smart Citation
“…Our latest results have shown that both series of glycosides are synthesized in roots of young marigold plants (Ruszkowski et al, 2003). The pathway of their biosynthesis is similar, although not identical, to the pathway occurring in green organs (Figure 2).…”
Section: Biosynthesis and Metabolism Of Oleanolic Acid Glycosidesmentioning
confidence: 70%
“…Lately (Ruszkowski et al, 2003) we have also demonstrated the occurrence of some amounts of ''glucuronides'' in roots of young marigold plants. In turn, ''glucosides'' are accumulated mainly in roots of grown and senescing plants.…”
Section: Introductionmentioning
confidence: 76%
“…In the same way, many agrochemicals and endogenous compounds are known to form uronic acid, in particular glucuronic acid, conjugates in animals [24]. However, glucuronide endogenous compounds are present in some plants such as marigold, Calendula officinalis , which is able to conjugate oleanolic acid to glucuronic acid [38]. Bockern et al [39] recently reported the formation of 4‐ n ‐nonylphenol glucuronide derivatives in wheat cell‐suspension cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Various terpenoids (Table 2) have been reported from the petroleum ether extract of C.officinalis flowers. They include sitosterols, stigmasterols [9], diesters of diols [10], 3monoesters of taraxasterol, ψ-taraxasterol, lupeol [11,12], erythrodiol, brein [13,14], ursadiol [15], faradiol-3-O-palmitate, faradiol-3-O-myristate, faradiol-3-O-laurate [16], arnidiol-3-O-palmitate, arnidiol-3-O-myristate, arnidiol-3-O-laurate, calenduladiol-3-Opalmitate, calenduladiol-3-O-myristate [17,18], oleanolic acid saponins: calenduloside A-H [19][20][21][22], oleanane triterpene glycoside: calendulaglycoside A, calendulaglycoside A6′-O-n-methyl ester, calendulaglycoside A6'-O-n-butyl ester, calendulaglycoside B, calendulaglycoside B 6′-O-n-butyl ester, calendulaglycoside C, calendulaglycoside C 6′-O-n-methyl ester, calendulaglycoside C 6′-O-n-butyl ester, calenduloside F6′-O-n-butyl ester, calnduloside G6′-O-n-methyl ester [18], glucosides of oleanolic acid (mainly found in roots of grown and senescing plants) I, II, III, VI, VII [23,24], and glucuronides (mainly found in flowers and green parts) F, D, D 2 , C, B and A [25]. One new triterpenic ester of olanane series has been isolated from flowers was cornulacic acid acetate from flowers [26].…”
Section: Terpenoidsmentioning
confidence: 99%